I am dolly parton eaudiobook - Meltzer, Brad (Ordinary People Change the World., 2022)
The legendary country musician, reading advocate, and philanthropist Dolly Parton is the 28th in the New York Times bestselling picture book biography series for ages 5 to 8, adapted for audio. This audiobook spotlights Dolly Parton, known for her beloved country songs, who has also sent over 150 million free books to children through her Imagination Library.    This friendly, fun biography series inspired the PBS Kids TV show Xavier Riddle and the Secret Museum. One great role model at a time, these books encourage kids to dream big. Included in each book are:    • A timeline of key events in the hero’s history    • Childhood moments that influenced the hero    • Facts that make great conversation-starters    • A character trait that made the person heroic and that readers can aspire to  You’ll want to collect each entry in this dynamic, informative series!